Dielectric tunability of (Ba0.90Ca0.10)(Ti0.75Zr0.25)O-3 ceramics - Chew, Khian Hooi; Chan, H.L.W.; Tang, X.G.; Wang, J. (AIP Publishing, 2004)
We have performed a study on the dielectric properties of (Ba0.90Ca0.10)(Ti0.75Zr0.25)O-3 bulk ceramics prepared by a sol-gel technique in the cooling temperature range from 400 to 213 K. The ceramics are found to exhibit an interesting dielectric response under the presence of a dc bias field. The field dependence of dielectric constant is stronger at Tapproximate toT(m) (T-m is the temperature of dielectric maximum) and the field-induced variation of dielectric constant Deltaepsilon is nonzero for T-T-m<150 K. One striking feature of these ceramics is that they possess a broad optimum value of figure of merit (as high as 200 at 30 kV/cm) between the temperature range from 295 and 330 K. At room temperature, the high tunability (K=60%), low-loss tangent (approximate to0.003), and large figure of merit (200), clearly indicate that these ceramics are suitable candidates for microwave applications. (C) 2004 American Institute of Physics.